234k views
1 vote
Solve for x. -6x+1=-41

2 Answers

2 votes

-6x+1=-41. -6x= -42. (-6x/6=x) (-42/6=7). X=7

User Xuuan Thuc
by
4.9k points
3 votes

Answer:


\boxed{ \bold{ \huge{ \boxed{ \sf{x = 7}}}}}

Explanation:


\sf{ - 6x + 1 = - 41}

Move 7 to right hand side and change it's sign


\dashrightarrow \sf{ - 6x = - 41 - 1}

Calculate


\dashrightarrow{\sf{ - 6x = - 42}}

Divide both sides by -6


\dashrightarrow{ \sf{ ( - 6x)/( - 6) = ( - 42)/( - 6) }}

Calculate


\dashrightarrow{ \sf{x = 7}}

Hope I helped!

Best regards! :D

User Jishad
by
6.1k points